Does dog acquisition improve physical activity, sedentary behaviour and biological markers of cardiometabolic health? Results from a three-arm controlled study - Emmanuel Stamatakis; Catherine Sherrington; Lauren Powell; Kate M Edwards; Adrian Bauman; Paul McGreevy; Anthony Podberscek; Brendon Neilly (BMJ Open Sport & Exercise Medicine)
Objectives Dog ownership has been associated with improved cardiometabolic risk factors, including physical activity. Most of the evidence originates from cross-sectional studies or populations with established disease. This study investigated changes in physical activity and other cardiometabolic risk factors following dog acquisition in a sample of 71 community-dwelling adults.Methods Participants self-allocated to three groups: 17 individuals acquired a dog within 1 month of baseline (dog acquisition), 29 delayed dog acquisition until study completion (lagged control) and 25 had no interest in dog acquisition (community control). Self-reported and thigh-worn accelerometer-based physical activity patterns, systolic and diastolic blood pressures, resting heart rate and VO2max were measured three times: baseline, 3 months and 8 months. Data were analysed using repeated measures analysis of covariance with owner age, season, sex and education included as covariates. Post hoc between-group tests were performed where there were significant overall effects (p<0.05).Results We found significant effects in mean daily steps (F(4,64)=3.02, p=0.02) and sit-to-stand transitions (F(4,66)=3.49, p=0.01). The dog acquisition group performed an additional 2589 steps (p=0.004) and 8.2 sit-to-stand transitions (p=0.03) per day at 3 months, although these effects were not maintained at 8 months. We found a significant effect in self-reported weekly walking duration (F(4,130)=2.84, p=0.03) among the lagged control group with an 80 min increase between 3 and 8 months (p=0.04). Other cardiometabolic risk factors were unchanged following dog acquisition.Conclusion Our study provides encouraging results that suggest a positive influence of dog acquisition on physical activity in the short term but larger and more generalisable controlled studies are needed.Trial registration number ACTRN12617000967381.